Surgical Pathology of Hepatobiliary Tumors - Cong, Wen-Ming.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book focuses on the pathological diagnosis of primary hepatic and bile duct tumors, and introduces the (3z(BThree Types and Six Sub-types(3y (Bclassification of hepatobiliary tumors. With more than 600 figures, including photographs and microscopy images, it highlights morphology, immunology and molecular pathology and their correlations with hepatic surgery and hepatic oncology. The book reviews the pathobiological characteristics of hepatic tumors and reveals the latest developments in this field. It is a valuable reference resource for hepatologists, pathologists and researchers.s
Immunohistochemistry of the liver tumors -- Molecular pathology of the liver tumors -- Tumor-like lesions of the liver -- Benign tumors of the liver -- Malignant tumors of the liver -- Children$1 (Bs tumors of the liver -- Tumors of the gallbladder -- Tumors of the extrahepatic bile duct -- Liver biopsy for the diagnosis of liver neoplasms.s
Keywords: Medicine; Hepatology; Oncology; Pathology; Medicine & Public Health; Oncology; Pathology; Hepatology